Manganese/copper bimetal-decorated biomass porous carbons as advanced electrode materials for high-performance supercapacitors. (25th November 2022) - Zhan, Yinbo; Bai, Jiaming; Guo, Feiqiang; Dong, Kaiming; Shu, Rui; Liu, Sha; Qiao, Qixia; Xu, Liya
Abstract: The development of green and inexpensive carbon materials with high electrochemical performance and good stability as electrode material in supercapacitor applications remains a great challenge. In this work, we report a novel type of Mn/Cu bimetal-decorated biomass porous carbons (AC@MnCu-X) prepared from an agricultural waste (peanut shell) to realize the combination of the double-layer capacitance of porous carbon materials and pseudocapacitance of metal compounds. The obtained carbon samples exhibit unique micro-mesoporous features with large surface area, and Mn/Cu nano strip structures are successfully decorated in the carbon matrix. The Mn/Cu nanostructures are mainly composed of CuO, MnO2 and CuMn2 O4, all of which are excellent pseudocapacitor electrode materials. Using as the electrode material, a high specific capacitance of 632 F/g was obtained by AC@MnCu-32 at a current density of 1 A/g in the three-electrode system with an excellent cycle life of 90 % capacitance retention after 10, 000 cycles. Besides, AC@MnCu-X samples were also used as electrodes to assemble asymmetric supercapacitors, which successfully lit up a light-emitting diode. AC@MnCu-32//AC exhibited the longest endurance among the three asymmetric capacitors, and its energy density reached 15.62 W h/kg at a power density of 625 W/kg. Highlights: CuMnx Oy decorated biomass porous carbons are synthesized. Large specific surface area over 2300 m 2 /g is retained for AC@MnCu-X. A high capacitance of 632 F/g is achieved at 1 A/g by the AC@MnCu-32 electrode. High capacitance retention of 90 % is achieved after 10, 000 cycles The LED bulb lit by AC@MnCu-32//AC still maintains strong brightness after 90 s.